Edukasi Perencanaan Karier Siswa Berbasis Mind-Mapping dan RIASEC di SMPN 2 Cisalak - Khoiriyah Isnaini Firmansyah Putri; Ghina Hanifah; Meita Sulistiyo; Rifaldini Rifaldini; Shabrina Fauzia Zahra (Lembaga Pengembangan Kinerja Dosen, 2026)
The career development of adolescents requires an accurate understanding of their potential, interests, and appropriate educational pathways; however, many students at SMPN 2 Cisalak still choose their next level of schooling without careful consideration due to limited access to career information. To address this issue, Guidance and Counseling students of Universitas Pendidikan Indonesia implemented a career planning education program based on Mind-Mapping and the RIASEC approach on August 15, 2025, involving 22 ninth-grade students as participants. The program employed educational socialization methods to introduce fundamental concepts of career planning, group discussions to explore students’ perceptions and experiences, Mind-Mapping activities to help them identify their strengths and educational goals, and the RIASEC assessment as an instrument to identify their interests and personality tendencies related to careers. The results of the Mind-Mapping and RIASEC assessments indicated diverse career interests, with dominant tendencies in the Social, Artistic, and Realistic types. Overall, this program enhanced students’ career awareness, self-confidence, and their ability to plan further education, while also providing a foundation for the school to develop more systematic and sustainable career guidance services.